Evaluation of 2 endodontic techniques used to treat human primary molars with furcation radiolucency area: A 48-month radiographic study - Coser, Rose Mary; Gondim, Juliana Oliveira [UNESP]; Giro, Elisa Maria Aparecida [UNESP] (Quintessence Publishing Co Inc, 2008)
Objective: To evaluate 2 techniques for the treatment of human primary molars with necrotic pulp and bifurcation bone loss by means of radiographic examination for 48 months. Method and Materials: Fifty-one mandibular primary molars were evaluated in children ranging from 4.5 to 6.5 years of age. The teeth with necrotic pulp and bifurcation bone loss were diagnosed by radiographic examination. The teeth were divided into 2 groups: group 1 (28 teeth)-pulpotomy technique using formocresol as a temporary dressing between sessions and coronal chamber obturation with zinc oxide-eugenol cement; and group 2 (23 teeth)-pulpectomy technique with calcium hydroxide paste as a temporary dressing between sessions and root canal obturation with a dense calcium hydroxide paste. Standardized radiographs were taken immediately after the fillings were completed and after 12, 24, 36, and 48 months. The radiographs were digitized and analyzed with software that outlined and measured the bifurcation radiolucency. Results: Bifurcation radiolucency reduced significantly or repaired completely for both treatments in the first 12 months. Minor radiographic reduction of the lesion was observed from 12 to 24 months, and no significant reduction of the remaining radiolucent area was observed from 24 to 48 months after treatment. Conclusion: The 2 endodontic techniques evaluated showed similar results. The main effect of treatment on the lesion repair was obtained in the first year after treatment.
Keywords: Dental radiography; Root canal therapy; Dental pulp necrosis; Calcium hydroxide; Molar; Primary tooth